MENDORONG KEBIASAAN BERKESENIAN UNTUK MERANGSANGKREATIVITAS ANAK-ANAK DUSUN JERINGAN, KULON PROGO, YOGYAKARTA - Tuasikal M. Amin (Asian Journal of Innovation and Entrepreneurship, 2015)
Inventiveness or creativity is a mental process that involves the appearance of anidea or draft (concept) new, or a new relationship between the idea and the existing draft.Creativity is strongly associated with the arts. Arting process will lead a person tocontinue to think creatively. Creativity that is needed by everyone can be stimulated bythe art. Observe the condition of children at Dusun Jeringan,Kecamatan Samigaluh, KulonProgo, Yogyakarta that is very few so often received less attention, especially related tocreativity when their brain is growing rapidly, the authors initiated doing a fun activity thataim to improve the process create on them. With this activity, children will be able tothink creatively, which means also develop the capacity to think.,